Ushul fiqh - INDONESIA._DEPARTEMEN_AGAMA (Proyek Pembinaan Prasarana dan Sarana Perguruan Tinggi Agama,Dirjen Binbaga Islam Depag, 1986)
Oen, Jil. 2=c.1-5/tr, jil.1=c.1/ir,jil.1,c.2/tr, jil.1=c.3/ tr, jil.1=c.4/why, jil 1=c.5/tr, jil.2=c.6/en, jil.1=c.5;jil.2=c.7-9/en, jil.1=c.6/en, jil.1=c.7/en, jil.1=c.8-9;jil.2=c.10/tr, jil.2=c.10/en, jil.1=c.10/ad, jil.2=c.12-13